Functional Skeletal Muscle Regeneration with Thermally Drawn Porous Fibers and Reprogrammed Muscle Progenitors for Volumetric Muscle Injury. Issue 14 (19th February 2021) - Jin, Yoonhee; Shahriari, Dena; Jeon, Eun Je; Park, Seongjun; Choi, Yi Sun; Back, Jonghyeok; Lee, Hyungsuk; Anikeeva, Polina; Cho, Seung‐Woo
Abstract: Skeletal muscle has an inherent capacity for spontaneous regeneration. However, recovery after severe injuries such as volumetric muscle loss (VML) is limited. There is therefore a need to develop interventions to induce functional skeletal muscle restoration. One suggested approach includes tissue‐engineered muscle constructs. Tissue‐engineering treatments have so far been impeded by the lack of reliable cell sources and the challenges in engineering of suitable tissue scaffolds. To address these challenges, muscle extracellular matrix (MEM) and induced skeletal myogenic progenitor cells (iMPCs) are integrated within thermally drawn fiber based microchannel scaffolds. The microchannel fibers decorated with MEM enhance differentiation and maturation of iMPCs. Furthermore, engraftment of these bioengineered hybrid muscle constructs induce de novo muscle regeneration accompanied with microvessel and neuromuscular junction formation in a VML mouse model, ultimately leading to functional recovery of muscle activity. Abstract : A bioengineered skeletal muscle construct is generated by culturing induced skeletal myogenic progenitor cells in a thermally drawn polycaprolactone porous fiber scaffold modified with decellularized muscle extracellular matrix. The hybrid composite fiber shows favorable mechanical and biochemical signals for muscle reprogramming and maturation. The bioengineered muscle construct repairs volumetric muscle loss injury via de novo muscle regeneration and functional restoration.